2016
DOI: 10.1016/j.enconman.2016.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Reducing lighting electricity use in underground metro stations

Abstract: Lighting systems are usually one of the largest electrical end-uses in underground metro stations. Taking into account that budget restrictions in publicly owned companies hinder energy efficiency retrofit projects that require high initial investments, affordable energy saving strategies are needed. This paper presents a low-cost approach for reducing lighting electricity use in underground stations, without affecting passengers' comfort or the metro operator's service. For this purpose, an adaptive lighting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Other solutions that help reduce electricity consumption are the use of light dimming systems within lighting sources. A study carried out in 115 metro stations in Barcelona found that by using intelligent lighting control systems, depending on the occupancy of the stations, a reduction of 36.22% in the basic consumption of lighting systems was achieved [32]. A similar percentage reduction in electricity (30%) was also identified in the case of street lighting that uses an adaptive lighting system depending on traffic conditions [33].…”
Section: Introductionmentioning
confidence: 88%
“…Other solutions that help reduce electricity consumption are the use of light dimming systems within lighting sources. A study carried out in 115 metro stations in Barcelona found that by using intelligent lighting control systems, depending on the occupancy of the stations, a reduction of 36.22% in the basic consumption of lighting systems was achieved [32]. A similar percentage reduction in electricity (30%) was also identified in the case of street lighting that uses an adaptive lighting system depending on traffic conditions [33].…”
Section: Introductionmentioning
confidence: 88%
“…This dimming strategy is meant to mainly offset the dirt accumulation on the luminaires; and luminaires are dimmed at the beginning of their maintenance period (and after they are cleaned) to ensure that minimum level requirements are met, but upper limits are not exceeded. This approach becomes very effective with low maintenance installations and dirt environments, such as metro stations, where energy saving can be up to 33% of the stations' baseline lighting consumption (Casals, Gangolells, Forcada and Macarulla, 2016) . Moreover, this strategy needs minimum investment, since the only extra equipment needed is a digital addressable lighting interface (DALI) controller.…”
Section: Maintenancementioning
confidence: 99%
“…First, the variable outdoor climate influences the energy consumption of the VAC system 28,29 . Second, the floor area determines the setting of lighting and other facilities 30 . Third, ridership can affect the energy consumption of ventilation fans and escalators and lifts (elevators) when these devices are running at variable frequencies.…”
Section: Introductionmentioning
confidence: 99%